LINGKUNGAN PEMBENTUKAN DAN DIAGENESIS BATUGAMPING DAERAH KEMANG BARU DAN SEKITARNYA, KABUPATEN SIJUNJUNG - Patonah, Aton; Isnaniawardhani, Vijaya (Fakultas Teknik Geologi Universitas Padjadjaran, 2014)
Carbonate rock is one of reservoir rock types in petroleum. It is interesting to study because its special characteristic, that is, it can change so easily that will affect to quality and quantity of reservoir. This research has been done at Kemang Baru area and around, Sijunjung Distric. Purposes of this research are to know texture and composition characteristic and to know what kind of environment deposition and diagenesis process involved as long as the formation. To get the information about that, petrography and Palinology methods are used. The result of this research shows that only 37 samples of carbonate type from 69 samples which have been analized. These are wackestone and mudstone. They have been formed at low energy environment and in reduction process which is characterized by present of pyrite in the rocks. To support the data, result of Palinology analysis, the rock have contained Dicolpopollis sp., Margocolporites sp., Palmaepollenites sp. and Psilatricolpites sp, berasosiasi dengan Acrostichum sp., Detloidospora sp., Hyphae sp., Inaperturisporites sp., Laevigatosporites sp., Verrucatosporites sp. Based on these, the rocks were formed at deep Lake.